Emerging biomarkers and frontier therapies: unveiling the role of endothelial dysfunction in cerebral small vessel disease - Sun, Kedi; Liu, Hui (Frontiers in Neurology, 2025)
Cerebral small vessel disease (cSVD), a major contributor to stroke, cognitive decline, and vascular dementia, accounts for around 25% of ischemic strokes and significantly impacts age-related neurological disability. Despite its clinical significance, the underlying mechanisms of cSVD remain incompletely understood, and therapeutic options are limited. Mounting evidence has pinpointed endothelial dysfunction as a central driver in cSVD pathogenesis, which disrupts blood–brain barrier (BBB) integrity, impairs cerebral blood flow autoregulation, and promotes neuroinflammation. The vascular endothelium, serving as a dynamic interface between blood and brain parenchyma, plays a crucial role in maintaining vascular homeostasis through functions like nitric oxide (NO)-mediated vasodilation, anti-thrombotic signaling, and immune regulation. In cSVD, chronic endothelial injury triggered by factors such as hypertension, oxidative stress, or genetic predisposition leads to microvascular rarefaction, pericyte loss, and gliosis, ultimately resulting in characteristic manifestations like white matter hyperintensities, lacunar infarcts, and cerebral microbleeds. Our review stands out by comprehensively integrating the latest research on emerging biomarkers and frontier therapeutic strategies specifically related to the cSVD-endothelium interplay. Recent breakthroughs in biomarker discovery, including novel circulating endothelial microparticles subtypes and advanced neuroimaging-derived biomarkers, offer unprecedented insights into endothelial health in cSVD. These biomarkers not only aid in early diagnosis but also enable more accurate risk stratification and monitoring of therapeutic responses. Concurrently, this review delves into the latest preclinical and clinical trial progress of innovative therapeutic strategies targeting endothelial repair. By bridging mechanistic insights with clinical translation, this review aims to highlight novel pathways for early intervention and personalized management of cSVD, thereby advancing the field beyond previous reviews that mainly focused on established knowledge. Relevant studies were retrieved from databases such as PubMed and Web of Science, covering the period up to 2025, to synthesize the latest evidence on endothelial dysfunction in cSVD. This review not only synthesizes current knowledge on endothelial dysfunction in cSVD but also critically evaluates the diagnostic and prognostic utility of emerging endothelial biomarkers and discusses recent therapeutic innovations, providing a more forward-looking perspective for researchers and clinicians.